PENGARUH KEBIJAKAN DIVIDEN, ROA (RETURN ON ASSETS), ROE (RETURN ON EQUITY) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN IDX30 - Nico; Hikmah (SCIENTIA JOURNAL, 2022)
The research is to determine the effect of dividend policy, ROA, and ROE on firm value inIDX30 companies.the research in this study uses the independent variables, namelydividend olicy, ROA and ROE with the dependent variable being firm value. This researchwas conducted on IDX30 index companies that have been listed on the Indonesia StockExchange (IDX) with A period from 2019 to 2021. The research was conducted using apurposive sampling method, from the results of using these method can be 13 companiesthat have met the criteria. From the results of trials conducted with the results of the t test,it shows that the ROE has a Positive and significant effect on firm value with a significant tvalue of 0.000 < 0.05 and the dividen policy variable along with ROA has no positive andsignificant effect on firm value.